2008
DOI: 10.1002/pssb.200879558
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin functionalized single‐walled carbon nanotubes

Abstract: The use of chemotherapeutic agents is nowadays limited by the damage they inflict to healthy tissues. Due to the fact that Carbon nanotubes (CNTs) possess the characteristic feature of being not degraded in the human body, they can be used to deliver small organic drug molecules into the diseased cells thus preventing normal tissue damages. Here, the functionalization of acid treated Single‐Walled CNTs with Cisplatin (Cis‐Diamminedichloroplatinum (CDDP)), a potent anticancer agent which suffers of toxic side‐e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The design of selective drug nanocarriers has been already broached using non-covalent methodologies and showing targeted killing activity in vitro and in vivo. 32,33 Indeed nanotubes [34][35][36][37][38][39][40][41] and nanohorns. 2,[42][43][44][45] have been applied to improve the uptake and selectivity of cisplatin, a well-known chemotherapeutic drug currently applied in the treatment of many solid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…The design of selective drug nanocarriers has been already broached using non-covalent methodologies and showing targeted killing activity in vitro and in vivo. 32,33 Indeed nanotubes [34][35][36][37][38][39][40][41] and nanohorns. 2,[42][43][44][45] have been applied to improve the uptake and selectivity of cisplatin, a well-known chemotherapeutic drug currently applied in the treatment of many solid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the integration between biomolecules and CNTs has shown that such nanostructures are strong candidates for various biomedical applications. , Molecular modeling has advanced to nanotechnology experimental studies. Quantum chemical calculations allow free design and detailed investigation of many systems projected for biological applications, especially drug delivery, frequently assisting experimentalists in this area. , Most of these works show that intermolecular forces such as van der Waals interactions and hydrogen bonds play an important role in the stability of drug delivery systems. , …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Most of these works show that intermolecular forces such as van der Waals interactions and hydrogen bonds play an important role in the stability of drug delivery systems. 11,13 Platinum drugs are still the most effective agents used in cancer treatment. Cisplatin (cis-DDP) is a widely known chemotherapy agent for several types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Using this phenomenon via wet chemistry, various anticancer therapeutics can be loaded in the tube interior. Carboplatin 47 or cisplatin 48,49 can be loaded by mixing with dispersed CNTs and stirring over a period of time. Thereaer the mixture is ltered and the excess of therapeutic material is rinsed off.…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%
“…The functionalization of MWCNTs and SWCNTs with cisplatin, another antineoplastic agent commonly used to treat a wide variety of tumors, has also been successfully demonstrated. 49,186 The newly reported use of PEGylated MWCNTs conjugated with the molecule angiopep-2 was used as a specic-targeted complex system to deliver the anticancer drug DOX to brain glioma tumors. 187 The study successfully showed through in vitro and in vivo tests that the MWCNT-PEG-angiopep-DOX system was suitable to treat glioma tumors in mice.…”
Section: Drug Deliverymentioning
confidence: 99%